Kegiatan Pengabdian kepada Masyarakat Penanggulangan Pengguna Narkoba di Desa Cibadak Kecamatan Cikupa Kabupaten Tangerang - Burhanudin Burhanudin; Tedy Subrata; Haryanto Haryanto (Nusantara Mengabdi Kepada Negeri, 2024)
Indonesia is a State of Law, this is stated in the explanation of the 1945 Constitution which states that; "The Indonesian state is based on law and not based on mere power." Law is a rule or regulation that regulates society. All behavior and actions of its citizens must be based on law, therefore, Indonesia is a country of law, obliged to carry out legal functions consistently as a means of upholding justice. As times progress, of course crime becomes more developed and organized. One of the problems that often comes to the surface in people's lives is crime in general, as currently we often encounter delinquency in the form of narcotics abuse. In Article 1 Paragraph 1 of Law of the Republic of Indonesia Number 35 of 2009 concerning NARCOTICS, the meaning of narcotics, namely substances or drugs derived from plants, either synthetic or semi-synthetic, which can cause a decrease or change in consciousness, loss of taste, reduce or eliminate pain, and can cause dependence, which are differentiated into groups as attached in the Law - The Narcotics Law is often used outside of medical and scientific purposes, which in the end will become a danger for the user, which in the end can also have an influence on the social order of the people of the nation and state. Combating narcotics abuse is not an easy thing to implement but the state is determined to eradicate it. Narcotics abuse covers all levels of society, including poor, rich, old, young and even children. Narcotics abuse has increased from year to year, which ultimately harms the nation's future cadres. One of the efforts made by the government to tackle the narcotics problem is through improvements in legal regulations. This improvement is very necessary because the influence of narcotics is very large on the survival of a nation.